Influence of testing position and age on measures of ankle proprioception. - Westlake KP; Culham EG (Advances in Physiotherapy, 2006)
Impaired proprioception affects balance and increases fall risk in older adults. However, age-related changes in proprioception are not always detected, possibly due to differences in testing protocols. This study aimed to determine the effect of testing position and age on three measures of ankle proprioception, using cross-sectional, repeated measures. The subjects were 14 older (78.9+/-5.0 years) and 14 younger (26.1+/-2.8 years) adults. Threshold to perception of passive movement (TPM) and passive and active joint position sense (JPS) absolute error (AE) were measured at the ankle in seated knee-extended, seated knee-flexed and standing positions. TPM and passive JPS AE were not dependent on testing position; both measures were significantly higher in older adults. Active JPS AE was dependent on testing position but was not dependent on age, and there was an interaction effect between position and age group. Post hoc analyses indicated an effect of position only in older adults with a higher mean active JPS AE in the seated knee-flexed position compared to the two other positions. Age-related changes in proprioception can effectively be determined using tests of TPM and passive JPS in any testing position. However, the ideal protocol may be the seated knee extension position for reasons of comfort and safety.